STUDI ISLAM INTER MULTIDISIPLINER (Model-Model Pendekatan dalam Kajian Ilmu Hadis Kontemporer) - Akhmat Taufik; Iqbal Kholidi (Al-Hasyimi: Jurnal Ilmu Hadis, 2024)
Currently, the study of religious texts cannot stand alone, but needs to involve other scientific disciplines. Because socio-religious problems are increasingly complex, while Islam, which originates from the teachings of the Koran and Hadith, must also dialogue with the realities and developments of the times. Therefore, the scientific interconnection paradigm has become a historical necessity, so that analyzes and conclusions drawn from religious texts can be more dialectical and comprehensive, as well as accommodating to the development of society. The study of hadith, both in the form of criticism of its authenticity and methods of understanding, including developments ranging from textualist to contextualist, from dogmatic to critical, from literal to liberal, is a concern for hadith thinkers. Whatever the variety and model of approach in understanding hadith, it is their appreciation and interaction with hadith as the second source of Islamic teachings after the Koran. In this article, the author tries to provide new offers from various sources, how to understand hadith (filth al-hadith) with an interconnection paradigm, namely linguistic, historical, sociological and anthropological. The purpose of this discussion is so that people's meaning of hadith does not experience stagnation and rigidity